In vivo antivascular endothelial growth factor treatment induces corneal endothelium apoptosis in rabbits through changes in p75NTR–proNGF pathway. Issue 11 (1st June 2018) - Gharbiya, Magda; Bruscolini, Alice; Sacchetti, Marta; Rosso, Pamela; Carito, Valentina; Segatto, Marco; Fico, Elena; Tirassa, Paola; Lambiase, Alessandro
Abstract : Intravitreal injection (IVT) of antivascular endothelial growth factor (anti‐VEGF) agents is widely used for the treatment of retinal vascular diseases. Recently, the injection of anti‐VEGF agents in the ocular anterior chamber has been proposed for the treatment of neovascular glaucoma and potential side effects on the corneal structures have been investigated with contrasting results. Increasing evidence has demonstrated that VEGF inhibition is associated with cellular apoptotic changes and that this effect may be mediated by alterations in nerve growth factor (NGF) pathway. In this study, we demonstrated that anterior chamber injection (IC), but not IVT injection of two different anti‐VEGF agents, aflibercept and ranibizumab, affects rabbit corneal endothelium in terms of survival and apoptosis and is associated with changes in endothelial expression of NGF precursor (proNGF) and p75 neurotrophin receptor (p75NTR) receptor. We observed an increase in corneal endothelial cell incorporation of trypan blue and expression of cleaved‐caspase 3 (c‐Casp3), p75NTR, and RhoA after IC injection of both anti‐VEGF drugs when compared with the vehicle. Our results showed that apoptosis induction by aflibercept was more pronounced when compared with that of ranibizumab. Aflibercept also mediated a significant increase in endothelial expression of proNGF when compared with the vehicle. In line with these data, IC administration of both anti‐VEGF agents induced the activation of apoptotic signals in endothelial cells, including an increase in c‐Casp3, decrease in Bad Ser 112 phosphorylation, and unbalance of AKT phosphorylation. These results demonstrated that administration of anti‐VEGF in the anterior chamber of rabbit affects endothelial cell survival by inducing apoptosis through alteration of NGF pathway. Abstract : In this study, we demonstrated that anterior chamber injection (IC), but not IVT injection of two different anti‐VEGF agents, affects rabbit corneal endothelium in terms of survival and apoptosis. The observed alterations are associated with changes in endothelial expression of NGF precursor and p75 neurotrophinp receptor.